Knowledge, attitude, and practice of using antibiotics among the community in Eastern Province, Saudi Arabia - Reem Hassan Elmahi; Nourah Ali Alrasheed; Ahmad Hassan Al Sayegh; Ali Ahmed Almobark; Nuzhat Banu; Mohammad Daud Ali (Wolters Kluwer Medknow Publications, 2023)
Objectives: The purpose of this study is to explore and evaluate the knowledge, attitude, and practice of using antibiotics among the community in the Eastern Province, of Saudi Arabia. Methods: A cross-sectional study was conducted, from February 2022 through March 2022, among people in Eastern Province, Saudi Arabia. Results: The study population was 753 of the Saudi community. The questionnaire used open-ended and multiple-choice questions. Out of 753 participants, only 254 (55.6%) think that antibiotics can treat a bacterial infection, whereas 163 (35.7%) and 82 (17.9%) think it treats viral and fungal infections respectively. 26 (5.7%) of the respondents think that they should be stopped when the antibiotics are finished, while 72 (15.8%) think that they should be stopped when the symptoms disappear. The most common side effect in the respondent's opinion was diarrhea 183 (40%), followed by 168 (36.76%) antibiotics resistance. The major reason for taking antibiotics without a prescription was found to be mild symptoms 28 (50.90%), adequate information 21 (38.18%), difficulty in taking appointments 17 (30.90%), long waiting hours during the hospital visits 15 (27.27%). 169 (36.9%) kept the leftover antibiotics for reuse. The most common antibiotics used for self-medication were found to be Amoxicillin and clavulanic acid 23 (41.8%), followed by Amoxicillin 9 (16.36%). Knowledge of antibiotic resistance was highest in the age group 20-30 (62.7%) (P < 0.05). Conclusion: People in Saudi Arabia show a high awareness of antibiotics' proper usage, and this returns to the great awareness campaign held by The Ministry of Health (MoH).